Validation of a blood marker for plasma volume in endurance athletes during a live‐high train‐low altitude training camp. Issue 7 (19th April 2018) - Lobigs, Louisa M.; Garvican‐Lewis, Laura A.; Vuong, Victor L.; Tee, Nicolin; Gore, Christopher J.; Peeling, Peter; Dawson, Brian; Schumacher, Yorck O.
Abstract: Altitude is a confounding factor within the Athlete Biological Passport (ABP) due, in part, to the plasma volume (PV) response to hypoxia. Here, a newly developed PV blood test is applied to assess the possible efficacy of reducing the influence of PV on the volumetric ABP markers; haemoglobin concentration ([Hb]) and the OFF‐score. Endurance athletes (n=34) completed a 21‐night simulated live‐high train‐low (LHTL) protocol (14 h.d ‐1 at 3000 m). Bloods were collected twice pre‐altitude; at days 3, 8, and 15 at altitude; and 1, 7, 21, and 42 days post‐altitude. A full blood count was performed on the whole blood sample. Serum was analysed for transferrin, albumin, calcium, creatinine, total protein, and low‐density lipoprotein. The PV blood test (consisting of the serum markers, [Hb] and platelets) was applied to the ABP adaptive model and new reference predictions were calculated for [Hb] and the OFF‐score, thereby reducing the PV variance component. The PV correction refined the ABP reference predictions. The number of atypical passport findings (ATPFs) for [Hb] was reduced from 7 of 5 subjects to 6 of 3 subjects. The OFF‐score ATPFs increased with the PV correction (from 9 to 13, 99% specificity); most likely the result of more specific reference limit predictions combined with the altitude‐induced increase in red cell production. Importantly, all abnormal biomarker values were identified by a low confidence value. Although the multifaceted, individual physiological response to altitude confounded some results, the PV model appears capable of reducing the impact of PV fluctuations on [Hb]. Abstract : Altitude is a confounding factor within the Athlete Biological Passport (ABP) due, in part, to a plasma volume (PV) contraction. Here, a newly developed PV blood test is applied to reduce the influence of PV contractions on ABP markers; haemoglobin concentration ([Hb]) and the OFF‐score. With the PV correction to the ABP reference limits are refined and the number of atypical [Hb] results is reduced. The application of the PV correction to the ABP has the potential to improve doping detection.